Low-Temperature Chemical Modification Challenges of Tallow, Butter, Palm Oil, and Palm-Based Biolubricants as Alternative Substitutes for Fossil Oils - Lenfa, Nuhu Buhari; Anterinwa, A.; Aliyu, B. A.; Yakubu, A. (Kwaghe International Journal of Sciences and Technology, 2025)
Plant-derived oils such as Shea butter and palm kernel oil—abundant in African countries, particularly Nigeria—exhibit significant potential for use in lubrication, industrial processes, and transportation applications. Similarly, animal fats including butter and tallow may serve as viable alternatives for biolubricant production. This study investigates the low-temperature performance—specifically the cloud and pour points—of biolubricant oils synthesized from palm oil, Shea butter, butter, and tallow using various laboratory-based methods, including methanolic solvent extraction. The research addresses the environmental impact of conventional lubricants, which often contain harmful substances such as heavy metals and are frequently disposed of indiscriminately. Experimental results demonstrate that the pour point of palm oil modified with polymethacrylate (TPMA) improved to –9.5 °C, compared to –5 °C without additives. The Shea butter–polymethacrylate blend (SBPMA) exhibited a pour point of –3.5 °C, while modified palm oil (POPMA) improved from 7.2 °C to –5 °C. Butter oil derived from milk (BOPPG) showed a cloud point of –5 °C, whereas the Shea butter–polypropylene glycol blend (SBPPG) had a pour point of –6 °C. Notably, the tallow oil–polypropylene glycol blend (TOPPG) exhibited the lowest cloud point at –8 °C. These improvements are attributed to the inclusion of polymethacrylate and polypropylene glycols, which enhance the oils’ low-temperature properties. The findings highlight the significance of chemical modification in overcoming the limitations of biolubricants under cold conditions, positioning them as more sustainable and environmentally friendly alternatives to fossil-based lubricants.